Escalating Students' Vocabulary Through Semantic Mapping Learning Model - Otoluwa, Moon Hidayati; Jolanda Debora Pilongo; Rosalin Tanaiyo; Herlina Usman (International Journal of Sustainable Applied Sciences, 2024)
The biggest obstacle for teachers and tutors is the lack of students' vocabulary. It causes students to feel difficulty understanding the meaning of English, particularly their performance in applying and developing four skills of English. Therefore, this research aims to enhance students' English vocabulary mastery through a semantic mapping learning model. This model was applied to seventh-grade students in the 7.2 class of MTs Al-Yusra Gorontalo, consisting of ten students. Classroom Action Research (CAR) was used as the method of this study. For collecting data, there are four phases of CAR used; they were planning, action, observation, and reflection. Two cycles were applied in this study because the first cycle did not improve students' vocabulary. Based on the data finding on cycle one, the scoring average of students' task results was 56,2. It is because 80% of students still got a low score, and 20% got a perfect score. The content of the task was about the questions of material "Noun". Then, in cycle two, it was applied by involving students in the classroom action; they were asked to present the result of their group discussion of semantic mapping of Noun material. After that, they did the second task, and the average of their score was 79,5. It could be concluded that the semantic mapping model greatly affected the students' mastery of the vocabulary taught by the teacher.